2023
DOI: 10.31545/intagr/162959
|View full text |Cite
|
Sign up to set email alerts
|

Study of the pore structure characteristics of soybean grain piles using image processing technology

Mengmeng Ge,
Guixiang Chen,
Chaosai Liu
et al.

Abstract: Pore structure is an important factor affecting the airflow distribution in a grain pile, and hence the variation in its structural parameters under different vertical pressures should be studied further. In this study, grain slice imaging and image processing technologies were comprehensively used to study the changes in the number, size, and shape of the pores in soybean grain piles under vertical pressures of 0, 50, 100, 150, 200, 250, and 300 kPa, and to explore the effects of vertical pressure on the poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…They quantitatively described the pore network structure of the grain porous medium. Ge et al [11] investigated the impact of vertical pressure on the pore structure of grain piles using grain slice imaging and image processing techniques. The results indicated that the pore area and pore diameter of the piled grain gradually decreased with increasing vertical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…They quantitatively described the pore network structure of the grain porous medium. Ge et al [11] investigated the impact of vertical pressure on the pore structure of grain piles using grain slice imaging and image processing techniques. The results indicated that the pore area and pore diameter of the piled grain gradually decreased with increasing vertical pressure.…”
Section: Introductionmentioning
confidence: 99%